2022
DOI: 10.3390/ijms232314914
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the Coagulation System in Peripheral Arterial Disease: Interactions with the Arterial Wall and Its Vascular Microenvironment and Implications for Rational Therapies

Abstract: Peripheral artery disease (PAD) is a clinical manifestation of atherosclerotic disease with a large-scale impact on the economy and global health. Despite the role played by platelets in the process of atherogenesis being well recognized, evidence has been increasing on the contribution of the coagulation system to the atherosclerosis formation and PAD development, with important repercussions for the therapeutic approach. Histopathological analysis and some clinical studies conducted on atherosclerotic plaque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 252 publications
0
5
0
Order By: Relevance
“…When the endothelium is damaged, platelets adhere to the vascular wall, inducing the formation of a platelet-rich thrombus through the binding of the platelet glycoprotein (GP) Iba receptor and the von Willebrand factor (vWF), expressed from the damaged endothelium. GPIba receptor also recruits circulating leucocytes binding integrins and P-selectin, perpetuating the inflammatory process [67,68]. Two platelet collagen receptors mediate platelet adhesion and activation [GPIa/IIa (integrin a2b1) and GPVI (immunoglobulin)] favoring the growth of the thrombus .…”
Section: Plaque Rupture and Atherothrombosismentioning
confidence: 99%
“…When the endothelium is damaged, platelets adhere to the vascular wall, inducing the formation of a platelet-rich thrombus through the binding of the platelet glycoprotein (GP) Iba receptor and the von Willebrand factor (vWF), expressed from the damaged endothelium. GPIba receptor also recruits circulating leucocytes binding integrins and P-selectin, perpetuating the inflammatory process [67,68]. Two platelet collagen receptors mediate platelet adhesion and activation [GPIa/IIa (integrin a2b1) and GPVI (immunoglobulin)] favoring the growth of the thrombus .…”
Section: Plaque Rupture and Atherothrombosismentioning
confidence: 99%
“…It is generally recommended that individuals with CVD take these medications, unless otherwise specified. Although clinical trials have not demonstrated the effectiveness of these drugs in individuals with type-2 diabetes who do not have CVD, they are still widely recommended ( 52 ). Furthermore, aspirin prophylaxis is a viable treatment option for individuals diagnosed with MetS who are at a relatively high risk of experiencing CVD-related events ( 53 ).…”
Section: Management Of Mets Risk Factorsmentioning
confidence: 99%
“…Coagulation factors such as tissue factor can also promote inflammatory responses by activating protease-activated receptors [55]; however, sex-dependent effects are unclear. The crosstalk between inflammation and coagulation factors contributing to PAD pathogenesis, recently reviewed elsewhere [56], highlights the complexity of this system. More studies are needed to fully appreciate the impact of sex-dependent EC thrombo-inflammatory processes in PAD.…”
Section: Leukocyte Trafficking and Inflammationmentioning
confidence: 99%